Ústavní smlouva a restrukturalizace Evropské unie - Prachař, Pavel; Týč, Vladimír, 1949-; Masarykova univerzita. Katedra mezinárodního a evropského práva (2006)
Tato diplomová práce se zaměřuje na reformu institucí Evropské unie, kterou představuje Evropská ústava. Jejím cílem je zhodnotit přínos změn, které by Ústava mohla znamenat pro budoucí vývoj jednotlivých institucí i Unie jako celku. Snaží se popsat a analyzovat jednotlivé změny, které Ústava do institucionálního rámce Unie vnáší. S největším důrazem se zabývá pozicí Evropské Komise. Na druhé straně ponechává stranou současný stav ratifikačního procesu Ústavy.
This diploma paper is focused on the institutional aspects of the reform introduced by the European Constitution. Its aim is to evaluate the contribution of the European constitution to the future development of the European Union as a whole and also for the evolution of the particular institutions. On the other hand it is not focused on the ratification process of the Constitution and the present state of this process. In short this diploma paper seeks to describe and analyze individual changes presented by the Constitution to the institutional framework of the Union. The position of the European Commission is particularly stressed.
Vedoucí práce: Vladimír Týč.
Diplomová práce (Mgr.)--Masarykova univerzita, Právnická fakulta, 2006.
Keywords: Evropská ústava; evropské právo; European law; diplomové práce